Implementasi Rumah Pengering Sederhana Pada Proses Pengeringan Keripik Tortilla Rumput Laut Poklahsar Swakarya Bersama - Kevin Hasiholan Lumban Tobing; Illa Rizianiza; Diniar Mungil Kurniawati; Samsu Dlukha Nurcholik (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The processing and marketing group (Poklahsar) Swakarya Bersama is one of the women's MSMEs located in Penajam Paser Utara (PPU) Regency. Poklahsar Swakarya Bersama is an MSME that drives regional superior products, namely processed seaweed. One of the superior products is seaweed tortilla chips which have been produced since 2019. The most important part in the production process of seaweed tortilla chips is drying. The drying process influences product quality, namely crispness, durability (shelf life) and aroma. The drying carried out by Poklahsar Swakarya Bersama still uses direct drying by the sun. The aim of the activities carried out is to implement a simple drying house which can improve product quality and shorten production time. The advantage of the simple designed drying house is that the heat produced comes from sunlight and does not require additional heat generating equipment. The equipment test results show that a simple drying house produces a faster drying rate compared to traditional drying. The drying rate of tortilla chip dough using a greenhouse effect dryer was 63.33 grams/hour. A simple drying house can also protect products from exposure to unfavorable environments so that the resulting products are cleaner and of better quality.